The lost world of the prophets: Old Testament prophecy and apocalyptic literature in ancient context - Walton, John H. (The Lost World Series, 2024)
Intro -- Title Page -- Contents -- Acknowledgments -- Introduction -- Part 1: Ancient Near East -- Proposition 1: Prophecy Is a Subset of Divination -- Proposition 2: Prophets and Prophecy in the Ancient Near East Manifest Similarities and Differences When Compared to Israel -- Part 2: Institution -- Proposition 3: A Prophet Is a Spokesperson for God, Not a Predictor of the Future -- Proposition 4: Prophecy in the Old Testament Is Not Monolithic but Developing -- Proposition 5: The Classical Prophets Are Champions of the Covenant in Times of Crisis -- Proposition 6: Prophecy Takes a Variety of Different Shapes After the Old Testament -- Part 3: Literature -- Proposition 7: Recognition of the Categories of Prophetic Message Help Us to Be More Informed Readers -- Proposition 8: Prophets Were Typically Not Authors -- Proposition 9: The Implied Audience of the Prophetic Books Is Not Necessarily the Audience of the Prophet -- Part 4: Methodological and Interpretive Issues -- Proposition 10: Distinction Between Message and Fulfillment Provides Clear Understanding of Prophetic Literature -- Proposition 11: Fulfillment Follows Oblique Trajectories -- Proposition 12: The New Testament Use of Old Testament Prophecy Focuses on Fulfillment, Not Message -- Proposition 13: Prophecy Carries Important Implications for Understanding God and the Future, but Our Ability to Forge a Detailed Eschatology with Confidence Is Limited -- Part 5: Apocalyptic -- Proposition 14: Apocalyptic Should Be Differentiated from Classical Prophecy -- Proposition 15: In Apocalyptic Literature, Visions Are Not the Message but the Occasion for the Message -- Proposition 16: New Testament Apocalyptic Operates by the Same Principles as Old Testament Apocalyptic -- Concluding Thoughts: A Reading Strategy -- For Further Reading -- Notes -- General Index -- Scripture Index.